Major stressful life events in adulthood and risk of multiple sclerosis. Issue 10 (7th March 2014) - Nielsen, Nete Munk; Bager, Peter; Simonsen, Jacob; Hviid, Anders; Stenager, Egon; Brønnum-Hansen, Henrik; Koch-Henriksen, Nils; Frisch, Morten
Abstract : Objective: It is unclear whether psychological stress is associated with increased risk of multiple sclerosis (MS). We studied the association between major stressful life events and MS in a nationwide cohort study using death of a child or a spouse or marital dissolution as indicators of severe stress. Methods: We created two study cohorts based on all Danish men and women born 1950–1992. One cohort consisted of all persons who became parents between 1968 and 2010, and another cohort consisted of all persons who married between 1968 and 2010. Members of both cohorts were followed for MS between 1982 and 2010 using data from the National Multiple Sclerosis Registry. Associations between major stressful life events and risk of MS were evaluated by means of MS incidence rate ratios (RR) with 95% confidence interval (CI) obtained in Poisson regression analyses. Results: During approximately 30 million person-years of follow-up, bereaved parents experienced no unusual risk of MS compared with parents who did not lose a child (RR=1.12 (95% CI 0.89 to 1.38)). Likewise, neither divorced (RR=0.98 (95% CI 0.89 to 1.06)) nor widowed (RR=0.98 (95% CI 0.71 to 1.32) persons were at any unusual risk of MS compared with married persons of the same sex. Conclusions: Our national cohort study provides little evidence for a causal association between major stressful life events (as exemplified by divorce or the loss of a child or a spouse) and subsequent MS risk.